1985
DOI: 10.1108/eb008128
|View full text |Cite
|
Sign up to set email alerts
|

Do‐it Yourself Consumers: Segmentation Insights for Retailers

Abstract: Over the last 40 years Do‐It‐Yourself (DIY) consumers have evolved from relative obscurity to a major multibillion dollar per year market. Research findings based on 403 DIY cases were used to develop insights for the formulation of retailer strategy. Types of projects undertaken and annual activity rates formed the basis of the investigation. Nine project categories were identified: carpentry, vehicle, painting, electrical, lawn and garden, plumbing, sewing, wall and floor covering, and masonry. Annual activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This viewpoint is in agreement with Browning and Zabriskie's (1985) study of do-it-yourselfers. Their study also supports the notion that do-it-yourself activity is related more to pursuit of satisfying leisure than economic need.…”
Section: Education and Market Implicationssupporting
confidence: 90%
“…This viewpoint is in agreement with Browning and Zabriskie's (1985) study of do-it-yourselfers. Their study also supports the notion that do-it-yourself activity is related more to pursuit of satisfying leisure than economic need.…”
Section: Education and Market Implicationssupporting
confidence: 90%
“…This segment is often operationalized as individuals who engaged in home or car maintenance activities within a specified period of time (e.g., preceding 12 months) (cf. Browning & Zabriskie, 1985;Hornik & Feldman, 1982). DIY activities are thought to be motivated by the rising costs of professional labor and recent availability of easy-to-use home improvement and maintenance products and outlets.…”
Section: Proposed Relationships Between Inherent Use Innovativeness Amentioning
confidence: 99%
“…DIY activities are thought to be motivated by the rising costs of professional labor and recent availability of easy-to-use home improvement and maintenance products and outlets. In addition, some observers have hypothesized that many do-it-yourselfers view projects as creative outlets and leisure activity (Browning & Zabriskie, 1985). The willingness to undertake home and car maintenance and repair projects involves problem-solving product use and requires a certain amount of risk taking in product use.…”
Section: Proposed Relationships Between Inherent Use Innovativeness Amentioning
confidence: 99%
“…Ahhough Toffler's contention is questionable in general, surveys have shown that in the past decade consumers have been doing more of their own household and car maintenance and repair than previously. 2 The increase in number and sales of home improvement and car parts retail stores supports the survey finding^.^.' The policy of providing free phone numbers for repair advice and understandable do-.…”
Section: Introductionmentioning
confidence: 68%